2014
DOI: 10.1002/acr.22247
|View full text |Cite
|
Sign up to set email alerts
|

Value of Questionnaire‐Based Screening as a Proxy for Neurocognitive Testing in Childhood‐Onset Systemic Lupus Erythematosus

Abstract: Objective. To investigate the utility of questionnaire-based assessment of cognitive function and behavioral/emotional symptoms to screen for neurocognitive dysfunction in childhood-onset systemic lupus erythematosus (cSLE). Methods. Forty children with cSLE and 24 healthy controls ages 10 -16 years were enrolled. Formal neurocognitive testing (FNCT) was done to determine cognitive performance in 4 key areas that appear to be sensitive to the adverse effects of cSLE: attention, working memory, psychomotor spee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Self-regulation can be succinctly defined as “control of attentional, emotional, and behavioral impulses,” and is regularly cited as a key component of social adaptation (Vega-Fernandez et al 2014; Duckworth and Carlson 2013). As such, poor self-regulation is most easily observed though difficulty sustaining attention, inability to effectively regulate behavioral impulses, and challenges in handling strong emotions through socially appropriate means.…”
Section: Introductionmentioning
confidence: 99%
“…Self-regulation can be succinctly defined as “control of attentional, emotional, and behavioral impulses,” and is regularly cited as a key component of social adaptation (Vega-Fernandez et al 2014; Duckworth and Carlson 2013). As such, poor self-regulation is most easily observed though difficulty sustaining attention, inability to effectively regulate behavioral impulses, and challenges in handling strong emotions through socially appropriate means.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, given the lack of a systematic screening options (i.e. physician perception and parent global impressions are insufficient to detect early cSLE associated cognitive changes) (16, 22) we consider the PedANAM-CPS indices to be an important tool for effective systematic screening for NCD in pediatric rheumatology clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of cognitive ability. Various approaches for the assessment of cognitive functioning have been proposed in the medical literature and for childhood-onset SLE (22). At present, there is no consensus about the most appropriate definition of a clinically relevant deficit or impairment in cognitive performance in childhood-onset SLE (23).…”
Section: Significance and Innovationsmentioning
confidence: 99%
“…In children, the one study that investigated a cognitive symptom questionnaire showed it was unable to detect disease [60]. In adults, symptom questionnaires have proven more useful as markers for NPSLE, with reported high sensitivity for the presence of disease, but only modest specificity [61].…”
Section: Experimental Biomarkersmentioning
confidence: 99%